Self-governance and forest resources - Ostrom, E. (Center for International Forestry Research, 1999)
Forest resources share attributes with many other resource systems that make difficult their governance and management in a sustainable, efficient and equitable manner. Destruction or degradation of forest resources is most likely to occur in open-access forests where those involved, or external authorities, have not established effective governance. Conventional theories applied to forest resources presumed that forest users themselves were incapable of organizing to overcome the temptations to overharvest. Extensive empirical research, however, has challenged this theory and illustrated the many ways that forest users themselves have devised rules that regulate harvesting patterns so as to ensure the sustainability of forest resources over time. There is now a large body of literature analysing common-pool resources such as many fisheries, irrigation systems and rangelands. A growing consensus exists in this literature concerning the attributes of common-pool resources and of resource users that enhance the probability that self-organization will occur. Many of these attributes seem also to help predict when forest users will self-organize. Forest users are more likely to devise their own rules when they use a forest that is starting to deteriorate but has not substantially disappeared, when some forest products provide early warning concerning forest conditions, when forest products are predictably available, and when the forest is sufficiently small that users can develop accurate knowledge of conditions. Self-organization is more likely to occur when forest resources are highly salient to users, and when users have a common understanding of the problems they face, have a low discount rate, trust one another, have autonomy to make some of their own rules, an d have prior organizational experience. These attributes of forests and of the user community affect the benefits and costs of organizing to protect and enhance forest resources. When users create organizations consistent with a set of design principles, they are likely to be able to sustain their own institutional arrangements over a long period of time. This growing consensus about the attributes of users and resources has been applied in the design of policies intended to enhance the participation of local users in the governance and management of common-pool resources, including many forests. Supporting further research - especially studies of forests and their users over time - is an important foundation for even more effective public policies in the future.